2022
DOI: 10.1186/s12873-022-00663-z
|View full text |Cite
|
Sign up to set email alerts
|

Portable stroke detection devices: a systematic scoping review of prehospital applications

Abstract: Background The worldwide burden of stroke remains high, with increasing time-to-treatment correlated with worse outcomes. Yet stroke subtype determination, most importantly between stroke/non-stroke and ischemic/hemorrhagic stroke, is not confirmed until hospital CT diagnosis, resulting in suboptimal prehospital triage and delayed treatment. In this study, we survey portable, non-invasive diagnostic technologies that could streamline triage by making this initial determination of stroke type, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 70 publications
0
16
0
1
Order By: Relevance
“…For potential clinical applications, it is meaningful to test if the proposed method can distinguish between and ischemic stroke [69].We make a new sample by embedding a 10-mm ischemia-mimicking phantom into porcine brain tissue. The contrast of the ischemia spot is −37% (within the reported range of ischemic stroke [60]), which means the microwave absorption in the spot is 37% lower than that in the porcine brain tissue.…”
Section: Distinguish Between Hemorrhagic and Ischemic Strokementioning
confidence: 99%
“…For potential clinical applications, it is meaningful to test if the proposed method can distinguish between and ischemic stroke [69].We make a new sample by embedding a 10-mm ischemia-mimicking phantom into porcine brain tissue. The contrast of the ischemia spot is −37% (within the reported range of ischemic stroke [60]), which means the microwave absorption in the spot is 37% lower than that in the porcine brain tissue.…”
Section: Distinguish Between Hemorrhagic and Ischemic Strokementioning
confidence: 99%
“…In the future, we may see the use of novel technologies for detecting stroke and LVO in ambulances or MSUs, such as ultrasound techniques [38], electroencephalography [39], near-infrared spectroscopy, microwave technology and volumetric impedance spectroscopy [40].…”
Section: Novel Diagnostic and Therapeutic Options In Ambulances And M...mentioning
confidence: 99%
“…These devices utilize a variety of technological approaches, including accelerometers, electroencephalography (EEG), microwaves, near-infrared, and transcranial Doppler ultrasound to detect LVOs [ 42 ]. Though the concept is exciting and shows promise, a systematic review published in 2022 concluded that these technologies require further development [ 43 ]. Further, the lack of large, multicenter studies and the heterogeneity of study designs and populations in available literature prevent definitive statements about their clinical utility [ 43 ].…”
Section: Emergency Medical Services and The Response To Strokementioning
confidence: 99%
“…Though the concept is exciting and shows promise, a systematic review published in 2022 concluded that these technologies require further development [ 43 ]. Further, the lack of large, multicenter studies and the heterogeneity of study designs and populations in available literature prevent definitive statements about their clinical utility [ 43 ].…”
Section: Emergency Medical Services and The Response To Strokementioning
confidence: 99%